2021
DOI: 10.1186/s12891-021-04324-3
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for managing the destruction of calcar femorale

Abstract: Background The calcar femorale was identified long ago. However, our current understanding of the calcar is insufficient, and its related concepts are sometimes confused. The calcar femoral is an important anatomical structure of the proximal femur, and its function can be overlooked. In trauma, tumors, or other diseases, the calcar femorale can be destroyed or changed pathologically. As a result, the mechanical structure of the proximal femur becomes destroyed, causing pathological fractures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The calcar femur is the internal weight-bearing system of the proximal femur, and plays an important role in the fracture of the proximal femur. By decreasing the force on the posterior and medial femur and increasing the force on the anterior and lateral femur [10,11], we found that with the gradual shortening of the proximal femur, the maximum stress on all four surfaces of the proximal femur decreased gradually. This suggests that the stability of the whole femur gradually increased with the shortening of the proximal femur.…”
Section: Discussionmentioning
confidence: 79%
“…The calcar femur is the internal weight-bearing system of the proximal femur, and plays an important role in the fracture of the proximal femur. By decreasing the force on the posterior and medial femur and increasing the force on the anterior and lateral femur [10,11], we found that with the gradual shortening of the proximal femur, the maximum stress on all four surfaces of the proximal femur decreased gradually. This suggests that the stability of the whole femur gradually increased with the shortening of the proximal femur.…”
Section: Discussionmentioning
confidence: 79%
“…Compressive stress cannot be transmitted through femur when medial calcar is disrupted, which results in loss of medial support of the fracture and subsequent screw cutout, collapse or lateral wall fracture. 22 The National Institute for Health and Care Excellence (NICE) recommends that SHS should be used in preference to an IMN in people with trochanteric fractures above and including the lesser trochanter for 31-A1 and 31-A2 fractures. 23 Therefore, for those ITF patients with effective medial calcar, SHS may be the preferred implant regardless of lateral wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…There was neither significant stress shielding nor stress concentration found in the remaining femur reconstructed by Stem A, as has been found in other types of stems. A possible explanation for these results might be that the position of Stem A was closer to the inferior region of the femoral neck, which has a strong trabecular architecture and thicker cortices to resist tensile or shearing forces applied to the neck through the head [27,28]. Inserting the stem into this area with a denser structure makes the fixation system more stable and more adaptive to the physiological stress transmission.…”
Section: Discussionmentioning
confidence: 99%